Brain Tumor Diagnostics and Therapeutics with Superparamagnetic Ferrite Nanoparticles - Hyder, Fahmeed; Manjura Hoque, S. (Contrast Media & Molecular Imaging, 2017)
Ferrite nanoparticles (F-NPs) can transform both cancer diagnostics and therapeutics. Superparamagnetic F-NPs exhibit high magnetic moment and susceptibility such that in presence of a static magnetic field transverse relaxation rate of water protons for MRI contrast is augmented to locate F-NPs (i.e., diagnostics) and exposed to an alternating magnetic field local temperature is increased to induce tissue necrosis (i.e., thermotherapy). F-NPs are modified by chemical synthesis of mixed spinel ferrites as well as their size, shape, and coating. Purposely designed drug-containing nanoparticles (D-NPs) can slowly deliver drugs (i.e., chemotherapy). Convection-enhanced delivery (CED) of D-NPs with MRI guidance improves glioblastoma multiforme (GBM) treatment. MRI monitors the location of chemotherapy when D-NPs and F-NPs are coadministered with CED. However superparamagnetic field gradients produced by F-NPs complicate MRI readouts (spatial distortions) and MRS (extensive line broadening). Since extracellular pH (pHe) is a cancer hallmark, pHe imaging is needed to screen cancer treatments. Biosensor imaging of redundant deviation in shifts (BIRDS) extrapolates pHe from paramagnetically shifted signals and the pHe accuracy remains unaffected by F-NPs. Hence effect of both chemotherapy and thermotherapy can be monitored (by BIRDS), whereas location of F-NPs is revealed (by MRI). Smarter tethering of nanoparticles and agents will impact GBM theranostics.